Preparation and Characterization of Gelatin-Based Mucoadhesive Nanocomposites as Intravesical Gene Delivery Scaffolds. (14th December 2014) - Liu, Ching-Wen; Chang, Li-Ching; Lin, Kai-Jen; Yu, Tsan-Jung; Tsai, Ching-Chung; Wang, Hao-Kuang; Tsai, Tong-Rong
Abstract : This study aimed to develop optimal gelatin-based mucoadhesive nanocomposites as scaffolds for intravesical gene delivery to the urothelium. Hydrogels were prepared by chemically crosslinking gelatin A or B with glutaraldehyde. Physicochemical and delivery properties including hydration ratio, viscosity, size, yield, thermosensitivity, and enzymatic degradation were studied, and scanning electron microscopy (SEM) was carried out. The optimal hydrogels (H), composed of 15% gelatin A175, displayed an 81.5% yield rate, 87.1% hydration ratio, 42.9 Pa·s viscosity, and 125.8 nm particle size. The crosslinking density of the hydrogels was determined by performing pronase degradation and ninhydrin assays. In vitro lentivirus (LV) release studies involving p24 capsid protein analysis in 293T cells revealed that hydrogels containing lentivirus (H-LV) had a higher cumulative release than that observed for LV alone (3.7-, 2.3-, and 2.3-fold at days 1, 3, and 5, resp.). Lentivirus from lentivector constructed green fluorescent protein (GFP) was then entrapped in hydrogels (H-LV-GFP). H-LV-GFP showed enhanced gene delivery in AY-27 cells in vitro and to rat urothelium by intravesical instillation in vivo . Cystometrogram showed mucoadhesive H-LV reduced peak micturition and threshold pressure and increased bladder compliance. In this study, we successfully developed first optimal gelatin-based mucoadhesive nanocomposites as intravesical gene delivery scaffolds.